THE RELATIONSHIP BETWEEN THE LONG IN HEMODIALIZATION WITH STATUS OF EXCESS VOLUME OF LIQUID IN CHRONIC KIDNEY FAILURE PATIENTS - Harianto, Susilo; Muhalla, Hafna Ilmy; Cahyani, Devi Purbandari Regita (Universitas Airlangga, 2021)
Chronic kidney disease is a chronic disease that progresses damage to the kidneys which disrupts the body's fluid and electrolyte balance which affects all body systems. PGK is currently it is one of the many diseases that have become a concern in the world including in Indonesia. One phenomenon that often occurs is an increase in fluid volume between two times of dialysis. The purpose of this study was to find out the long relationship between hemodialysis and excess fluid volume status in patients with chronic renal failure in the Hemodialysis room at Ibnu Sina Gresik Hospital. This was an analytical study with a correlative analytic design. Data were collected by using the contingency coefficient. The result of this study shows that older respondents underwent <1 year of hemodialysis with excess fluid status >2,5 BB post HD as much 81,2%, which is more dominant than patients who undergo > 1-year hemodialysis with excess fluid status >2,5 BB post HD as much 58% of the total resulting in p-value 0,103 where p>0,05 so it can be concluded that there is no long relationship to undergo hemodialysis with excess fluid volume status in patients with chronic kidney disease. It is expected that patients undergoing hemodialysis can be more obedient to the recommended diet so that it does not cause other complications and can improve the quality of life patients